Conversations with Gorbachev : on perestroika, the Prague Spring, and the crossroads of socialism - Gorbachev, Mikhail Sergeevich, 1931-2022 (Columbia University Press, 2002)
"Mikhail Gorbachev and Zdenek Mlynar were friends for half a century, from the time their paths first crossed as students in 1950. Although one was a Russian and the other a Czech, they were both ardent supporters of communism and socialism. One took part in laying the groundwork for and carrying out the Prague Spring; the other opened a new political era in Soviet and world politics." "In 1993 they decided that their conversations might be of interest to others and so they began to tape-record them. This volume is the product of that "thinking out loud." A historical document in its own right, the book is a record of two friends trying to explain to one another their views on the problems and events that determined their destinies. From reminiscences of their starry-eyed university days to reflections on the use of force to "save socialism" to contemplation of the end of the Cold War, here is a more revealing picture of Gorbachev than we have seen before."--Jacket